(untitled) (Research, Society and Development, 2022)
Objective: To assess the prevalence of factors associated with a severe ESAS score of 7 points or more in one or more of its domains. Method: Patients admitted to medical clinic wards for three days or more were evaluated. Sociodemographic and clinical data and the ESAS questionnaire were collected. The ESAS has 10 domains, one of which is related to depression. ESAS was used with 10 domains and 9 domains (no depression domain). ESAS was classified as severe (with a score equal to or greater than 7 points in at least one domain) and not severe. Multivariate statistical evaluation identified the independent variables associated with severe and severe ESAS without the depression domain. Results: 93 patients were included in the study, 40 (43.01%) were female. The mean age was 53.11 ± 18.28 years, religion was considered very important by 74 (79.56%), non-white ethnicity was identified in 70 (75.83%) and depression in 16 (17.20%). Severe ESAS was present in 52.69% of patients. The final multiple logistic regression model showed self-reported depression as the only factor associated with severe ESAS in the 10-domain protocol (p = 0.02; OR = 4.30 (95% CI 1.21-15.24)) and as the only factor associated with severe ESAS without the depression domain (p = 0.04; OR = 3.41 (95% CI 1.01-11.53)). Conclusion: The prevalence of severe ESAS was high and the only independent factor associated was self-reported depression. It is necessary to incorporate the assessment of symptoms into the routine of hospital care, especially in patients with self-reported depression.